O orgulho como laboratório para a ciência da natureza humana de Hume - Julio Andrade Paulo (2010)
In this dissertation, I argue that Hume, in discussing pride in Book 2 of the Treatise of Human Nature, wants to show the applicability and therefore the quality of his science of human nature as a way to explain human phenomena in a simple and general way. He had expressed at the very beginning of Book 2 the hypothesis that pride and other passions in the human mind arise indirectly as a result of a double relation, one of them between impressions and the other between ideas. The relation between ideas involves the idea of the cause of pride and the idea of self,which is the object of pride. The relation between impressions involves an impression of pleasure produced by the cause of pride and passion of pride (which Hume had argued that this is an agreeable indirect violent impression of reflection that has self as its object). I argue that Hume,when examining pride in Book 2, does not want to achieve a definition of pride by correcting the definitions of previous philosophers. Taking this passion as a parameter for the other indirect passions, he has in mind, essentially, the aim of proving his hypothesis concerning the doublerelation of impressions and ideas, which involves the passions and their causes, thus bringing credibility to his science of human nature, which was intended as an enhancement of the socalled moral philosophy to reach the level at which natural philosophy had come with the simpleand general formulations of Newton.